The Distribution of the Agentive Nominalizer of the Suffixes -er and -an - Denistia, Karlina; Alip, Francis Borgias (Universitas Sanata Dharma, 2014)
This study focuses on the suffixes –er and -an because these suffixes are the most commonly used suffixes in daily life and thus really productive. There are three problems formulated for this topic: (1) What are the characteristics of stems receiving suffixes –er and -an? (2) What meanings are introduced by suffixes –er and –an? (3) What are the distributions of the allomorphs of suffixes –er and -an? The data of this study are morphemes and affixes. Hornby’s Oxford Advanced Learner’s Dictionary (year of 2000) is used. Finally, the present researcher found that the suffixes –er and an are attached to certain verbs, adjectives, and nouns. The suffix -an are not attached to verbs. The suffix -er is mostly attached to transitive verbs to create three possibilities of meaning. There is only one meaning of the suffix –er when it is attached to an adjective, and eight meanings of the suffix –er when it is attached to certain nouns. For suffix -an, there are three meanings when it is attached to adjectives and five meanings when it is attached to nouns. There are two meanings of the suffix -an when it is attached to nouns. The allomorph of the suffix -er are –or, -eer /ɪər/, and –ier /ɪər/, while the allomorphs of the suffix -an are –ian /ʃn/, -ian /ɪən/, and –ean /ɪən/. Keywords: morpheme, derivational suffixes, an agentive nominalization, stem, allomorph